2014
DOI: 10.3109/14767058.2014.908842
|View full text |Cite
|
Sign up to set email alerts
|

CRP levels in extremely low birth weight (ELBW) septic infants

Abstract: Highest CRP values in <1000 g infants increase in levels comparable to full terms, but with a 24-h delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…Previous research has described a lesser CRP response in CoNS neonatal infections, generally compared to S. aureus , GBS, E. coli and Candida spp. infections . While this may be the case when investigating all the neonatal infections in which these organisms were identified, our data demonstrate that CoNS is able to elicit a marked CRP response, as this was the most commonly identified organism in our sample of neonates with CRP >100 mg/L.…”
Section: Discussionmentioning
confidence: 64%
“…Previous research has described a lesser CRP response in CoNS neonatal infections, generally compared to S. aureus , GBS, E. coli and Candida spp. infections . While this may be the case when investigating all the neonatal infections in which these organisms were identified, our data demonstrate that CoNS is able to elicit a marked CRP response, as this was the most commonly identified organism in our sample of neonates with CRP >100 mg/L.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies concluded that CoNS might induce a less sustained inflammatory response than gram-negative bacterial sepsis [ 13 , 14 ]. However, our findings do not suggest a statistically significant difference in peak CRP’s values in infants with CoNS compared to other pathogens, however this is not statistically significant given the small number of gram-negative infections.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have assessed the use of CRP for the diagnosis of early-onset sepsis in term and late-preterm infants [ 13 15 ]. In these populations, two CRP values of < 10 mg/L have a negative predictive value of 93 to 97% [ 2 , 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…В своем исследовании авторы впервые показали, что чем меньше гестационный возраст ребенка и меньше масса тела при рождении, тем менее выражено повышение СРБ [13]. По мнению Dritsakou и соавт., СРБ не является корректным диагностическим тестом при диагностике сепсиса у новорожденных с ЭНМТ и ОНМТ в связи с недостаточной реактивностью печени у глубоконедоношенных детей вследствие ее незрелости, в отличие от более зрелых недоношенных и доношенных новорожденных [14].…”
Section: Discussionunclassified